When Two Feathers fell from the sky - Verble, Margaret (Mariner Books, an imprint of HarperCollinsPublishers, 2021)
"Louise Erdrich meets Karen Russell in this deliciously strange and daringly original novel from Pulitzer Prize finalist Margaret Verble: set in 1926 Nashville, it follows a death-defying young Cherokee horse-diver who, with her companions from the Glendale Park Zoo, must get to the bottom of a mystery that spans centuries"--